Immigrant workforce and agriculture productivity: evidence from Italian farm-level data. (23rd July 2021) - Baldoni, Edoardo; Coderoni, Silvia; Esposti, Roberto
Abstract: This paper investigates the farm-level relationship between total factor productivity (TFP) and presence and composition of immigrant workers. A theoretical model expressing how immigrant workforce influences productivity is developed and an explicit and consistent representation of the so-called 'diversity hypothesis' is derived. A dynamic panel specification is estimated, and the respective econometric issues are discussed. The analysis is applied to a balanced panel of Italian professional farms extracted from the Farm Accountancy Data Network over the period 2008–2015. The use of micro-level data in such assessment allows to take the wide heterogeneity across farms into account. Results suggest that, when productivity dynamics and farm heterogeneity are accounted for, empirical support to the diversity hypothesis can be found in Italian professional agriculture.